Designing Strategy for Islamic Boarding School (Pondok Pesantren) in Indonesia - Mehdar Badrus Zaman; Anisa Nabela Syusfa (LPPM STIT Nurussalam OKU Timur. Sidogede, Kec. Belitang, Kabupaten Ogan Komering Ulu Timur, Sumatera Selatan 32382, 2023)
Islamic Education Institutions play a very important role in building good moral, principles and Islamic characteristics toward Indonesian society. One of the distinctive Islamic institutions and considered as the oldest one is Islamic Boarding Schools (pesantren). This paper aims to design a strategy to be implemented in such Islamic Education Institution to enhance the Islamic education for the benefit of the students and whole Muslims in Indonesia. In further discussion, firstly this paper presents an overview of Islamic education in pesantren and secondly, it discusses the strategy of pesantren itself. The strategy in such institution must be set based on Islamic values and seen from Islamic perspectives. Any method or principles adopted from external values also need to be adapted and shaped to be more Islamic. However Islam doesnot overlook any principles as long as it is not contrary to Islamic principles and laws.